View Single Post
Old 2020-11-08, 15:49   #4
Alberico Lepore
 
Alberico Lepore's Avatar
 
May 2017
ITALY

3×7×23 Posts
Default

if I am not wrong this is the demonstration

((2*(3*N-1)/8-3*y+1)/24)=x*(x+1)/2-(y+1)/2*(y-1)/2/2
,
p*q=N
,
q=2*(3*x+1-(x-y+1))+1
,
p=2*(3*x+1-(x-y+1))+1-(4*y-2)
,
p*q=N=(8*M+1)/3
,
(p-2)*(q+2)=(8*(M-3*y)+1)/3
,
(2*M-3*y+1)=(2*(M-3*y)+3*y+1)
,
3*(((2*(3*N-1)/8-3*y+1)/24)+3*x*(x+1)/2)+1=12*x*(x+1)/2+1-3*(y+1)/2*(y-1)/2/2




please feedback

Last fiddled with by Alberico Lepore on 2020-11-09 at 05:51
Alberico Lepore is online now   Reply With Quote